Profiling early adopters of ‘iSupport-Portugal’: a country-specific version of a worldwide adapted digital support program for informal caregivers of people with dementia - Teles, Soraia; Alves, Sara; Ribeiro, Oscar; Freitas, Alberto; Ferreira, Ana; Paúl, Constança (Frontiers in Psychology, 2024)
Introduction Informal caregivers are the backbone of dementia care. iSupport is a World Health Organization digital support program for caregivers of people with dementia (PwD) that has been culturally adapted in several countries. iSupport was previously assessed for its feasibility in Portugal, and this country-specific version is now being utilized as a remote measurement tool (RMT). It constitutes the first internationally developed iSupport platform that is technically and scientifically enhanced to collect data on sociodemographic, clinical, and psychosocial variables of dementia care dyads. This paper characterizes the early adopters of iSupport-Portugal and discusses its exploration as a RMT. Methods Cross-sectional data were collected between February and July 2023 from users registering on isupport-portugal.pt. To characterize caregivers and PwD, eligibility was limited to unpaid caregivers assisting community dwelling PwD (n = 173). Data were collected through self-administered instruments in users’ accounts. Caregivers completed psychosocial measures on burden, anxiety, depression, quality of life, desire to institutionalize and usage of community services. Textual data on caregivers’ needs underwent content analysis. Results Among the early adopters of iSupport-Portugal (n = 365), 52.3% were informal caregivers, while 44.7% were health/social care professionals or others. Most caregivers were female (82.7%), middle-aged (M 51.7 years), highly educated (M 15.3 years) and supporting a parent (70.5%). Caregivers cared for a median of 24 h/week and 60.8% lived with the PwD. Neuropsychiatric symptoms were reported for 94.1% of PwD, who scored as moderately dependent (Barthel Index: M 14.0). Significant burden was reported by 88.4% of caregivers (≥21 on ZBI-22). Among caregivers scoring borderline or abnormal (≥8 on HADS) for anxiety, depression, or both (75.5%), 30.8% sought mental health counseling. Caregivers supporting a PwD not using community services scored higher on anxiety (p = 0.003), and depression (p = 0.009). Text data revealed unmet practical, emotional, and informational needs. Discussion iSupport-Portugal has garnered fair initial interest from caregivers, particularly from those who are children, highly educated, and employed. Early adopters exhibited significant psychological distress, and both practical and emotional needs, which contrast with limited use of support services for themselves and the PwD. iSupport-Portugal shows promise for descriptive research on care dyads, particularly among newer generations of caregivers.